Mutant p53 Expression Of Oral Transformed Epithelium Cell In Rats Injected By Benzo[A]Pyrene - Pertami, Sawitri Dwi indah; Sudiana, I Ketut; Budhy, Theresia Indah; Palupi, Retno; Arundina, Ira (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Benzopyrene is a polycyclic aromatic hydrocarbons (PAHs) compound that can cause transformation of normal cells into malignant in order to its genotoxic,mutagenic,and carsinogenic ability. DNA mutation in tumor suppressor genes p53 make cells immortal which results in cell transformation and develops into malignancies. This study consist of five groups including the control group (without benzopyrene injection) and 4 treatment groups injected with benzopyrene each for 4 weeks (P1), 6 weeks (P2), 8 weeks (P3) and 10 weeks (P4). Therefore, the mutant p53 expression was calculated and analyzed statistically with the One Way Anova Test. There was signifficance difference in mutant p53 expression of oral transformed epithelium cell injected by benzopyrene (p=0.000) and the highest expression was at 10th week. It can be concluded that the mutant P53 expression of oral transformed epithelium cells in rats was increased after injected by benzopyrene